Ultra‐Sensitive and Selective Electrochemical Bio‐Fluid Biopsy for Oral Cancer Screening. Issue 5 (18th January 2021) - Xiao, Zuohui; Huang, Chenyan; Jiang, Shengjie; Kong, Xiangyu; Teng, Yunfei; Niu, Bo; Zhu, CongCong; Xin, Weiwen; Chen, Xiaohui; Wen, Liping; Wei, Yan; Deng, Xuliang
Abstract: The early diagnosis of recurrence and metastasis is critically important for decreasing the morbidity and mortality associated with oral cancers. Although liquid biopsy methods hold great promise that provide a successive "time‐slice" profile of primary and metastatic oral cancer, the development of non‐invasive, rapid, simple, and cost‐effective liquid biopsy techniques remains challenging. In this study, an ultrasensitive and selective electrochemical liquid biopsy is developed for oral cancer screening based on tracking trace amounts of cancer biomarker by functionalized asymmetric nano‐channels. Detection via antigen–antibody reactions is assayed by evaluating changes in ionic current. Upon the recognition of cancer biomarker antigens in bio‐fluids, the inner wall of nano‐channel immobilized with the corresponding antibodies undergoes molecular conformation transformation and surface physicochemical changes, which significantly regulate the ion transport through the nano‐channel and help achieve sensitivity with a detection limit of 10 –12 g mL −1 . Furthermore, owing to the specificity of the monoclonal antibody for the antigen, the nano‐channel exhibits high selectivity for the biomarker than for structurally similar biological molecules present in bio‐fluids. The effectiveness of this technique is confirmed through the diagnosis of clinical cases of oral squamous cell carcinoma. This study presents a novel diagnostic tool for oral cancer detection in bio‐fluids. Abstract : The ultra‐sensitive and selective oral cancer screening is realized using functionalized asymmetric nano‐channels with a detection limit of 10 −12 g mL −1 . More importantly, the effectiveness of this technique is confirmed through the clinical diagnosis of oral squamous cell carcinoma. This study presents a novel diagnostic tool for oral cancer detection in bio‐fluids.